ANALISIS PERBEDAAN TINGKAT KEPUASAN TERHADAP KUALITAS PELAYANAN BENGKEL AHASS DAN BENGKEL YAMAHA. (Studi Kasus pada Bengkel AHASS Naga Sakti Ngesrep dan Yamaha Mataram Sakti Setiabudi - Adrian Dwinanda; Apriatni Endang Prihatini (Universitas Diponegoro, 2017)
Motorcycle is one of the most used vehicles by Indonesian people, many companies in the automotive field has grown. Honda and Yamaha are motor products with the most sales in Indonesia. Both companies give the best innovation to fulfill the needs of its customers. Customers have there own choices in choosing which products to use, but customer’s consideration not only on motorcycle products, but after sales services provided. Both companies also try to provide the best service in providing maintenance services and motorcycle repair on the workshop. The service strategies provided by both companies in their official workshop are given in order to give satisfaction to their customers.The research aims to determine the level of satisfaction of the official service shop from AHASS Naga Sakti and Yamaha Mataram Sakti. Type of this research is descriptive analysis, with population of 100 respondents on AHASS Naga Sakti workshop customers and 100 respondents on Yamaha Mataram Sakti customers in Semarang. Sampling in this research using purposive sampling technique. Data were collected through questionnaires. Data analysis method used by Importance performance analysis and Independent sample t-test by using SPSS application.The results of this study indicate that customer satisfaction level of Yamaha Mataram has a higher score higher with 89.35% than AHASS Naga Sakti customer satisfaction level with score 83.11%.we suggest for both companies have to improve the quality of service on several dimensions of existing services. AHASS Naga Sakti has to improve the quality of the service of tangible dimension , while on Yamaha Mataram Sakti has to improve the quality of service on the dimension of Reliability. This aims to increase customer satisfaction in both companies to keep customers using the services of both companies